2017
DOI: 10.1097/md.0000000000007526
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of brain natriuretic peptide and β-endorphin plasma concentration changes in patients with acute left heart failure and atrial fibrillation

Abstract: Rationale:This study aims to evaluate the diagnostic value of beta-endorphin (β-EP) and brain natriuretic peptid (BNP) plasma concentrations for the early diagnosis of acute left heart failure and atrial fibrillation.Patient concerns:A total of 45 patients were included. These patients comprised 23 male and 22 female patients,and 20 healthy subjects who underwent physical examinations in the Outpatient Department during the same periodwere included and assigned to the control group.Diagnoses:The diagnos stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…BNP mean concentration ± SD showed a statistically significant association with heart failure grades and increased with increasing in grades getting its peak value in patients with grade IV heart failure (1182.697±284.931) with a P-value of 0.0001. There is another preceding study demonstrated that the BNP concentration elevated with the advancement of heart failure grade [27].Further studies also found same results as other studies also found similar results, showing that increase of homocysteine levels associated with increase NT-pro-BNP levels through a link with impaired mitochondrial fatty oxidation, in two contrasted populations [28,29].Other previous study show compatible results with this study, which reported that higher level of BNP in patients with class 4 and the mean level was (8270.2±6116.9) with a P=value of < 0.05 [26].…”
Section: Discussionsupporting
confidence: 77%
“…BNP mean concentration ± SD showed a statistically significant association with heart failure grades and increased with increasing in grades getting its peak value in patients with grade IV heart failure (1182.697±284.931) with a P-value of 0.0001. There is another preceding study demonstrated that the BNP concentration elevated with the advancement of heart failure grade [27].Further studies also found same results as other studies also found similar results, showing that increase of homocysteine levels associated with increase NT-pro-BNP levels through a link with impaired mitochondrial fatty oxidation, in two contrasted populations [28,29].Other previous study show compatible results with this study, which reported that higher level of BNP in patients with class 4 and the mean level was (8270.2±6116.9) with a P=value of < 0.05 [26].…”
Section: Discussionsupporting
confidence: 77%
“…However, even if BNP is specific and sensitive for detecting early acute cardiac failure, despite the increase, the APN‐D levels remained within a normal rang and did not reach clinically significant levels (Feng et al. ), suggesting the presence of adaptation mechanisms in spearfishermen due to their high‐level of training.…”
Section: Discussionmentioning
confidence: 99%
“…In many pathological conditions, such as the ventricular volumetric load and pressure overload, BNP concentration will be increased in the blood ( Kou et al, 2016 ). The higher severity of heart failure will result in higher concentration of BNP ( Hahn et al, 2016 ; Feng et al, 2017 ). BNP shows good specificity in differential diagnosis of CHF ( Jin et al, 2018 ), cardiogenic dyspnea ( Golshani et al, 2016 ), and lung-derived respiratory distress ( Sun et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%